2011
DOI: 10.17221/171/2009-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Quality of shiitake stipe steamed bun

Abstract: Shiitake [Lentinula edodes (Berk.) Pegler] stipe was incorporated into steamed bun. Quality attributes including the specific volume, colour and sensory evaluation, and taste components in shiitake stipe steamed buns were analysed and compared with those of white steamed buns. With 2% and 5% additions of shiitake stipe flour, specific volumes of steamed buns increased by 5.8% and 5.0%, respectively. White steamed buns contained more reducing sugar, fat, and protein whereas fiber and soluble polysaccharide cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Most amino acids, especially leucine, glutamic and aspartic acids, were increased in formulated nuggets (Table 2), which was influenced by shiitake addition. Tseng et al (2011) reported that coarse SP (100 g) was composed of about 2490 mg of free amino acids, thus it directly increased total free amino acid content in white steamed buns with increasing amount of SP. In view of taste components, classified by sensory taste intensity evaluation (Table 2), the increase in aspartic and glutamic amino acids (approximately 15.61 %), which contributed to the monosodium glutamate-like taste, led to enhance umami flavor in formulated nuggets (Yamaguchi et al 1971).…”
Section: Proximate Composition and Amino Acid Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Most amino acids, especially leucine, glutamic and aspartic acids, were increased in formulated nuggets (Table 2), which was influenced by shiitake addition. Tseng et al (2011) reported that coarse SP (100 g) was composed of about 2490 mg of free amino acids, thus it directly increased total free amino acid content in white steamed buns with increasing amount of SP. In view of taste components, classified by sensory taste intensity evaluation (Table 2), the increase in aspartic and glutamic amino acids (approximately 15.61 %), which contributed to the monosodium glutamate-like taste, led to enhance umami flavor in formulated nuggets (Yamaguchi et al 1971).…”
Section: Proximate Composition and Amino Acid Profilementioning
confidence: 99%
“…Most panelists preferred nuggets containing SP around 2-3 %. This is because shiitake mushrooms are high in the non-essential amino acids; glutamic and aspartic acids, and the 5 0 -nucleotides, especially 5 0 -guanosine monophosphate (5 0 -GMP), which were recognized as umami taste compounds (Tseng et al 2011). Dermiki et al (2013) showed the enhanced umami and salty characteristics in cooked meat products added with natural umami-containing ingredients such as yeast extract, shiitake extract, low-salt soy sauce and beef stock paste.…”
Section: Colormentioning
confidence: 99%
“…Tseng et al . () reported that steamed bun added 0–5% shiitake stipe flour had higher specific volume than that added 10% shiitake stipe flour.…”
Section: Resultsmentioning
confidence: 98%
“…The buns were then placed in the proofer (Fresh FX11Bss, Malaysia) at 35ᴼC for proofing and initial fermentation of 12 to 15 minutes (Tseng, Yang, Lee and Mau, 2011). After being shaped, the conventional method for steaming was conducted for about 7 to 8 minutes in a steaming pot with a boiling wok under it.…”
Section: Steamed Bun Makingmentioning
confidence: 99%
“…All the panelists completed the questionnaires. The sensory attributes of the steamed buns that were evaluated consisted of color, aroma, sweetness, texture and overall acceptability using a 9point hedonic scale with 1, 5 and 9 representing extremely dislike, neither like nor dislike and extremely like respectively (Tseng et al, 2011).…”
Section: Sensory Evaluationsmentioning
confidence: 99%